Entrepreneurship Management for Education Financing Management of Modern Islamic Boarding Schools - Handayani Dewi, Dyah (The International Journal of Education Management and Sociology, 2022)
This research is to analyze the concept of entrepreneurship strategic planning, Implementation of entrepreneurship strategic in managing education financing, Evaluation of entrepreneurship strategic of Modern Islamic Boarding School. The contribution and impact of strategic entrepreneurship of Modern Islamic Boarding Schools in financing and developing education. This research method uses a qualitative approach. Data collection techniques using interviews, participant observation and documentation studies. The results of this study indicate that: (1). Planning by functioning the resources owned, by marketing products, through emotional and professional approaches, making financial projections, determining member investment capital, making production based on sales results (2). Implementation of the program, motivating teachers and staff by the leadership (3). Evalusai startegis entrepreneurship in Pondok Moderen every three months, annually with management supervision (4) The contribution and impact of strategic entrepreneurship on financing, the budget of all educational programs, facilities and facilities, human resource development, scholarships for students, the availability of cheap education.